Analisis Perbandingan Metode Autentikasi pada Mobile Banking menggunakan Usability Testing dan User Experience Questionnaire (UEQ) (Studi pada BTN Mobile dan Livin' by Mandiri) - Gusti Agzalia; Aryo Pinandito; Hanifah Muslimah Az-Zahra (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2023)
Authentication is an action taken to prove a user's identity when the user wants to enter a system or application, one of which is a mobile banking or m-banking application. Each m-banking application uses a different authentication method, for example, the authentication method for the BTN Mobile and Livin' by Mandiri applications. In the BTN Mobile application, the authentication method used is the mToken method. This method is a method of sending a special numeric code via SMS to the Mobile phone of a user who wants to make a financial transaction. Unlike the authentication method on the BTN Mobile application, the Livin' by Mandiri application uses a very common authentication method, namely the PIN (Personal Identification Number) method. This research was conducted to analyze comparisons related to the efficiency of the authentication method used in the BTN Mobile and Livin' by Mandiri applications using scenario testing. In addition, a comparative analysis of user experience was also carried out using the User Experience Questionnaire (UEQ) for both applications. In the data collection process, scenario testing was carried out with 11 participants and questionnaires were distributed to 52 participants. From the analysis process carried out, it was found that the Livin' by Mandiri application was more efficient and faster than the BTN Mobile application. In addition, the Livin' by Mandiri application also gives a better impression regarding the user experience, especially on the novelty aspect compared to the BTN Mobile application.